TINGKAT KAPASITAS PETANI DALAM PENERAPAN SISTEM AGROFORESTRI DI DESA TAMANSARI KECAMATAN TAMANSARI KABUPATEN BOGOR - Mardiana, Lyna; Susdiyanti, Tun; Salampessy, Messalina L (Universitas Nusa Bangsa, 2017)
The capacity of farmers is one of the causes of the unoptimization of the application of agroforestry system so that it will affect the low performance of the agroforestry system in generating social, economic and ecological benefits for the community. This study aims to determine the level of farmer capacity in the application of agroforestry system. Data collected using the instrument: (a) Observation (observation), (b) Structured and free interviews. The research variables are managerial capacity, technical capacity and social capacity. The result of the research shows the level of farmer capacity in high category, but the farmer is weak in establishing external cooperation with outsiders to support their farming activities such as traders, input production providers, formal financial institutions / banking, and other information and innovation institution. Recommendations for increased farmers 'capacity through: participatory training and counseling, improving the quality of assisting roles and researchers in empowerment processes, improving farmers' access to capital inputs and markets so that farmers are not dependent on middlemen, and improving coordination between government agencies and stakeholdersÂ Keywords: Behaviors, Private Forest, Dangiang Village, supporting and inhibiting factors, SWOT Analysist